2017
DOI: 10.1177/2325967117734496
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pretest Exercise on Baseline Computerized Neurocognitive Test Scores

Abstract: Background:Baseline neurocognitive assessment plays a critical role in return-to-play decision making following sport-related concussions. Prior studies have assessed the effect of a variety of modifying factors on neurocognitive baseline test scores. However, relatively little investigation has been conducted regarding the effect of pretest exercise on baseline testing.Purpose/Hypothesis:The aim of our investigation was to determine the effect of pretest exercise on baseline Immediate Post-Concussion Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Covassin et al [7] reported that verbal memory neurocognitive scores worsened following maximal exercise, but there were no differences on composite scores of visual memory, motor processing speed or reaction time. Retrospectively, pretest exercise on baseline neurocognitive measures yielded similar results with worse verbal and visual memory, reaction time and a greater prevalence of invalid tests [8].…”
mentioning
confidence: 65%
“…Covassin et al [7] reported that verbal memory neurocognitive scores worsened following maximal exercise, but there were no differences on composite scores of visual memory, motor processing speed or reaction time. Retrospectively, pretest exercise on baseline neurocognitive measures yielded similar results with worse verbal and visual memory, reaction time and a greater prevalence of invalid tests [8].…”
mentioning
confidence: 65%
“…Another study demonstrated that strenuous exercise protocols are associated with improved post-concussive symptoms; however, neurocognitive recovery declined from day 2 to day 10 after initiation of the protocol (13). Studies in healthy children, adolescents and adults have shown that strenuous activity immediately to up to 3 h before testing can negatively affect cognitive assessment (34, 35). However, in other healthy and neurologic populations, high-intensity exercise seems to have a greater impact on brain plasticity and brain health (3644).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were also not permitted to test if they had exercised within 3 hours of their testing session. 30 Test administration was altered for a few tests to improve accuracy. The average time to complete the coordination task was used because all participants were able to achieve this task in ,4 seconds.…”
Section: Methodsmentioning
confidence: 99%